Everything I've never said - Wheeler, Samantha (St Lucia, Queensland : University of Queensland Press, 2018)
From bestselling author Samantha Wheeler comes a heartfelt story about a girl who longs to communicate. Ava would like nothing more than to tell her family she loves them, particularly her big sister, Nic. But Ava has Rett syndrome - she can't talk, can't nod her head, can't even point at a communication card. She understands everything, but no one understands her. When tragedy strikes her family, Ava becomes even more determined to talk. But it's not until she meets occupational therapist Kieran and new friend Aimee that she is hopeful for change - and to find her voice at last. A powerful novel about a subject rarely tackled - young people with disabilities and the families who love and support them.
The Children’s Book of the Year Awards.
Keywords: Family life fiction; Families -- Fiction; Rett syndrome -- Juvenile fiction; Occupational therapists -- Juvenile fiction; Life change events -- Juvenile fiction; Sisters -- Juvenile fiction; Australian